Peningkatan Keaktifan Dan Hasil Belajar IPA MelaluiModel Pembelajaran Make A Match pada SiswaKelas V SDN Gentan 03 TAHUN 2015/2016 - Sari, Rudyta Zulita (2016)
This study aims to determine whetever the learning model Make A MAatch can enhance the activity and results of students of class V SDN Gentan 03 in 2015/2016. Subject of research that fifth grade teachers and students of class V SDN Gentan 03 with a number of 32 students. This research is class act. This study was conducted during two cycles or four meetings. Collecting data through interviews, observation, tes evaluation an documentation. As for the validity of the data using triangulation and triangulation of data collection techniques. The results showed an increase liveliness that is, dare to ask if it does not understand something on a pre-cycle 34,37% increase in the second cycle 75,78% , trying to find a variety of information required in the pre-cycle increased 38,28% increase in the second cycle 82,03%, express opinions on a pre-cycle 39,06% increased in the second cycle of 82,8% , taking the test/assignment at the pre-cycle 50% increase in the second cycle into 89,84%. Learning model of Make A Match also improve student learning outcomes, as evidenced at the stage of pre-cycle, there were 13 students who pass the KKM or 40,62% and increase in the second cycle of 30 students who completed the KKM or 93,75%. Conclusion of the study the model of learning Make A Match can enhance the activity and results of students of class V SDN Gentan 03 in 2015/2016. Keywords :activity of learning, learning outcomes, science, Make A Match